PENINGKATAN KETERAMPILAN GURU SMP NEGERI 2 TINAMBUNG MELALUI EDUKASI OPTIMALISASI PEMANFAATAN ALAT PERAGA - Syamsuri Syamsuri; Hafsah Hafsah; Hasria Alang (LPPM Universitas Bina Bangsa, 2023)
Less than optimal use of teaching aids is an indicator that the learning process is still conventional. Visual aids are media that can help teachers to visualize something so that it can be understood by students. The aim of this activity is to provide training in order to improve teacher skills through education on optimizing the use of teaching aids to support learning in schools. This activity was carried out at SMP Negeri 2 Tinambung, the activity participants were subject teachers. This activity method consists of three stages, namely planning, implementation and evaluation. Planning begins with observation to find out the problems faced by partners. Then proceed with the implementation, namely providing material, and evaluation in the form of a questionnaire which aims to measure the increase in participants' knowledge as well as reflection to find out the weaknesses and shortcomings of PKM activities. As a result of observations, it was found that partners still did not understand and were not optimal in using teaching aids, so this training was deemed necessary. Providing activity material using methods are lectures and demonstrations. The evaluation results show that there has been an increase in participant knowledge from 65% to 90%. This means that this activity has been proven to increase participants' knowledge and experience